Strandings of cetaceans and sea turtles in the Alboran Sea and Strait of Gibraltar: A long-term glimpse at the north coast (Spain) and the south coast (Morocco) - Rojo-Nierto, Elisa; Álvarez, Pablo; Morote, Elvira; Burgos, Macarena; Montoto Martínez, Tania; Sáez-Jiménez, Jorge; Toledano, Francisco (2011)
A total of 13 species of cetaceans and three species of marine turtles were found in this study. Data were collected by eight independent and self-regulated stranding networks, providing information about 1,198 marine mammal (10 odontocetii, three mysticetii and one phocidae) and 574 sea turtle stranding events between 1991 and 2008. Trends in the strandings were analysed in relation to species composition and abundance, and their geographic and seasonal distribution. The most abundant species recorded were the striped dolphin and the loggerhead turtle. Some of the strandings, such as the humpback whale, harbour porpoise, hooded seal and olive ridley turtle, were considered 'rare' because their distribution did not match the pattern of the study. When the north and south coasts in the study area were compared, pilot whales stranded more frequently in the north, while delphinid species stranded more in the south coast, and loggerhead turtles stranded more frequently in the north while leatherback turtles stranded more in south coast. © 2011 Museu de Ciències Naturals. En este estudio se registraron un total de 13 especies de cetáceos y tres especies de tortugas marinas, proviniendo los datos de redes de voluntarios que prestan asistencia en los varamientos. Se recogió información de 1.198 mamiferos marinos (10 odontocetos, tres misticetos y un fócido) y 574 tortugas marinas entre los años 1991 y 2008. Se analizaron las tendencias de los varamientos en relación a la composición de especies, su abundancia y su distribución geográfica y estacional. Las especies más comunes fueron el delfín común y la tortuga boba. Algunos de los varamientos, como la ballena jorobada, la marsopa común, la foca de casco o la tortuga olivácea, pueden considerarse "anómalos" puesto que su distribución se escapa a los patrones del estudio. Comparando la costa norte del área de estudio con la sur, los calderones y tortugas bobas vararon con mayor frecuencia en la costa norte, mientras que las especies de delfines y las tortugas laúd ...